2020
DOI: 10.1039/d0nr05199c
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium based carbide–oxide heterogeneous V2O5@V2C nanotube arrays for high-rate and long-life lithium–sulfur batteries

Abstract: Due to its ultra-high theoretical energy density, low cost, and environmental friendliness, lithium-sulfur batteries have become a potentially strong competitor for next-generation energy storage devices. Looking for a host material...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The XPS spectra of the obtained V 2 C/V 2 O 5 /CNTs are displayed in Figure b–d. The V 2p spectrum reveals the characteristic peaks of V 5+ species in V 2 O 5 at 517.5 (2p 3/2 ) and 525.0 (2p 1/2 ) eV as well as V 4+ species in V 2 C at 516.6 (2p 3/2 ) and 524.2 (2p 1/2 ) eV . The C 1s spectrum shows the subpeaks for C–C, C–O, CO, and O–CO bonds within 284–290 eV, while notably, a small peak can be perceived at 282.8 eV corresponding to the V–C bonding in V 2 C .…”
Section: Resultsmentioning
confidence: 95%
“…The XPS spectra of the obtained V 2 C/V 2 O 5 /CNTs are displayed in Figure b–d. The V 2p spectrum reveals the characteristic peaks of V 5+ species in V 2 O 5 at 517.5 (2p 3/2 ) and 525.0 (2p 1/2 ) eV as well as V 4+ species in V 2 C at 516.6 (2p 3/2 ) and 524.2 (2p 1/2 ) eV . The C 1s spectrum shows the subpeaks for C–C, C–O, CO, and O–CO bonds within 284–290 eV, while notably, a small peak can be perceived at 282.8 eV corresponding to the V–C bonding in V 2 C .…”
Section: Resultsmentioning
confidence: 95%
“…Further, they also added hydrochloric acid to the solution to adjust the pH, which is conducive to the uniform nucleation of S particles on the matrix. Wang et al 73 have simultaneously dispersed the V 2 O 5 @V 2 C and S in the ethanol, where the S is uniformly loaded on the surface of V 2 O 5 @V 2 C nanotubes.…”
Section: One-step Deposition Method Melt-diffusion Methodmentioning
confidence: 99%
“…Wang et al 70 reported that in the VO 2 (p)-V 2 C host, the constitution of VO 2 (p) and V 2 C as well as the unique morphology collectively ensure that the VO 2 (p)-V 2 C/S cathode shows a 69.1% capacity retention at 2 C after 500 cycles. Wang et al 73 introduced that the MX-VPNAs host can show a synergistic effect of the excellent catalytic ability of V 2 O 5 , high carrier mobility of V 2 C, and long-term stable adsorption of V 2 O 5 @V 2 C with a high structural stability to LiPSs. Thus, the V 2 O 5 @V 2 C/S cathode exhibits a first capacity of 1173 mAh•g −1 at 0.2 C and a cycle decay of 0.047% for 1000 times.…”
Section: Two-step Deposition Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the electrons from the fracture of S 8 ring combines with lithium ions to form the soluble high-order polysulfide Li 2 S n (4≤n≤8) in the electrolyte. Subsequently, this longchain polysulfide converts to non-soluble short-chain polysulfide Li 2 S 2 /Li 2 S [11,12]. Meanwhile, the Li 2 S n dissolves in the electrolyte and diffuses to the anode side, and probably combines with lithium ions on the anode to form solid Li 2 S 2 /Li 2 S [13,14].…”
Section: Introductionmentioning
confidence: 99%